Asparagine Synthetase in Cancer: Beyond Acute Lymphoblastic Leukemia - Chiu, Martina; Taurino, Giuseppe; Bianchi, Massimiliano G.; Kilberg, Michael S.; Bussolati, Ovidio (Frontiers in Oncology, 2020)
Asparagine Synthetase (ASNS) catalyzes the synthesis of the non-essential amino acid asparagine (Asn) from aspartate (Asp) and glutamine (Gln). ASNS expression is highly regulated at the transcriptional level, being induced by both the Amino Acid Response (AAR) and the Unfolded Protein Response (UPR) pathways. Lack of ASNS protein expression is a hallmark of Acute Lymphoblastic Leukemia (ALL) blasts, which, therefore, are auxotrophic for Asn. This peculiarity is the rationale for the use of bacterial L-Asparaginase (ASNase) for ALL therapy, the first example of anti-cancer treatment targeting a tumor-specific metabolic feature. Other haematological and solid cancers express low levels of ASNS and, therefore, should also be Asn auxotrophs and ASNase sensitive. Conversely, in the last few years, several reports indicate that in some cancer types ASNS is overexpressed, promoting cell proliferation, chemoresistance, and a metastatic behaviour. However, enhanced ASNS activity may constitute a metabolic vulnerability in selected cancer models, suggesting a variable and tumor-specific role of the enzyme in cancer. Recent evidence indicates that, beyond its canonical role in protein synthesis, Asn may have additional regulatory functions. These observations prompt a re-appreciation of ASNS activity in the biology of normal and cancer tissues, with particular attention to the fueling of Asn exchange between cancer cells and the tumor microenvironment.